2022
DOI: 10.1136/bmjopen-2021-060107
|View full text |Cite
|
Sign up to set email alerts
|

Psychological experience of inpatients with acute pancreatitis: a qualitative study

Abstract: ObjectiveThis study aimed to better understand the psychological experiences of inpatients with acute pancreatitis (AP).DesignWe used a qualitative descriptive study design to capture patients with AP’s thoughts, feelings and behavioural responses.SettingWe conducted this study in the gastroenterology departments of two tertiary hospitals in Eastern China.ParticipantsWe used a convenience sampling approach to recruit 28 inpatients with AP from 1 August 2020 to 25 December 2020. The interviews were audio-record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Pain, digestive symptoms are among the causes of depression ( 35 ). In addition, lack of knowledge about pancreatitis, uncertainty about the disease and fear of recurrence, life stress and lack of family support can all contribute to emotional exhaustion ( 36 ). These patients may present with fatigue, feelings of helplessness, lack of interest in things, guilt and shame and despair ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pain, digestive symptoms are among the causes of depression ( 35 ). In addition, lack of knowledge about pancreatitis, uncertainty about the disease and fear of recurrence, life stress and lack of family support can all contribute to emotional exhaustion ( 36 ). These patients may present with fatigue, feelings of helplessness, lack of interest in things, guilt and shame and despair ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In qualitative studies, Fear of pain and special treatments, worry about work and the burden on family members were often mentioned by patients with AP [ 8 , 16 ]. Besides, a qualitative study was conducted in 28 AP patients, they also expressed the fear of disease recurrence and further deteriorate, and they had to change their living habits to prevent a recurrence of the disease [ 13 ]. The contents of fear in AP patients were basically consistent with the items of the FoP-Q-SF.…”
Section: Methodsmentioning
confidence: 99%
“…However, they are not used in acute diseases, and none of them, to our knowledge, specifically assessed FoP in AP patients. The FoP-Q-SF has been validated in a variety of diseases, and our qualitative studies reported that the fear content of patients with AP was similar to the items in the FoP-Q-SF [ 13 ]. In order to effectively observe the psychological effect of FoP in AP patients, we need a suitable assessment tool.…”
Section: Introductionmentioning
confidence: 99%
“…This aligns with the discoveries made by Ma. 24 Prior research has indicated that competent psychological counseling can significantly alleviate patients' negative feelings, such as sadness and anxiety. It can also raise patients' self-efficacy, improve their compliance with treatment and nursing care, and facilitate positive changes in their health behaviors.…”
Section: Diagnosis Phase: Provide Patients With Accurate Information ...mentioning
confidence: 99%